PENGEMBANGAN BAHASA ANAK USIA DINI MELALUI METODE ROLE PLAYING - SUCI MIDSYAHRI AZIZAH (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
This research is based on the problem of suboptimal development of children's language. The objective to be achieved is to obtain a picture of children's language development in TK Tunas Indah through the application of the role playing method which is formulated as follows: (1) What is the condition of children's language development before applying the method of role playing in TK Tunas Indah? (2) What is the process of applying the role playing method in improving children's language development at TK Tunas Indah? (3) what extent is the improvement in the language development of TK Tunas Indah children after applying the role playing method? and (4) What constraints do teachers experience in implementing the role playing method? The research method used is Classroom Action Research (CAR) to improve the learning process of children's language development through the application of the role playing method. Classroom Action Research was carried out in two cycles, with the subjects of group A children in TK Tunas Indah, totaling 15 children. From the results of the implementation and observations made, there was a significant increase, especially in the second cycle. It is recommended for teachers that language development is further optimized, both in learning, implementing and evaluating learning. For further researchers, it is expected to make research on the development of children's language through other methods.